Integrated reporting of intellectual capital and financial performance of deposit money banks in Nigeria - Onyia, Obiageli Priscillia; Emengini, Steve Emeka; Chinyere, Ori Bertha; Usman, Odoma Ademu (International journal of economic perspectives, 2025)
The study examined the effect of integrated reporting of intellectual capital on the performance of listed deposit money banks in Nigeria. The specific objectives are to: (i) examine the effect of integrated reporting of structural and relational capital efficiency on return on assets and return on equity of the sector under study. The study employed an ex-post facto research design. Secondary data was used for the period of i5 years (2008-2023). Population of the study comprises the twenty-two listed deposit money banks. The study adopted judgemental sampling method in the selection of twelve banks. Preliminary tests of the database were carried out using augmented dickey-fuller unit root test at 5% level of significance. Data were presented using descriptive statistics and correlation analysis while least square regression model was used to test the hypotheses at 5%level of significance. Integrated reporting of Structural and human capital efficiency has a positive and significant effect on return on assets and return on equity while Integrated reporting of Relational capital efficiency showed both negative and positive insignificant relationship with return on assets and return on equity of listed banks in Nigeria. The study concluded that integrated reporting of intellectual capital components in the money deposit banks financial statements will positively affect their performance at the long run and thereby suggest that bank managers should strive to expose their employees to research and development and other training programs that will automatically improve their performance.